Longitudinal Changes in Quality of Life and Rates of Progressive Visual Field Loss in Glaucoma Patients - Medeiros, Felipe A.; Gracitelli, Carolina P.B.; Boer, Erwin R.; Weinreb, Robert N.; Zangwill, Linda M.; Rosen, Peter N. (Ophthalmology (Rochester, Minn.), 2015)
To evaluate the association between longitudinal changes in quality of life (QoL) and rates of progressive visual field loss in glaucoma. Prospective observational cohort study. We recruited 322 eyes of 161 patients with glaucomatous visual field loss from the Diagnostic Innovations Glaucoma Study followed for an average of 3.5±0.7 years. All subjects had National Eye Institute Visual Function Questionnaire (NEI VFQ)-25 performed annually and standard automated perimetry (SAP) at 6-month intervals. Subjects were included if they had a minimum of 2 NEI VFQ-25 and ≥5 SAP during follow-up. Evaluation of rates of visual field change was performed using the mean sensitivity (MS) of the integrated binocular visual field (BVF). Rasch analysis was performed to obtain final scores of disability as measured by the NEI VFQ-25. A joint longitudinal multivariate mixed model was used to investigate the association between change in NEI VFQ-25 Rasch-calibrated scores and change in BVF sensitivity. Potentially confounding socioeconomic and clinical variables also were analyzed. The relationship between change in NEI VFQ-25 Rasch-calibrated scores and change in binocular SAP MS. There was a significant correlation between change in the NEI VFQ-25 Rasch scores during follow-up and change in binocular SAP sensitivity. Each 1-dB change in binocular SAP MS per year was associated with a change of 2.9 units per year in the NEI VFQ-25 Rasch scores during the follow-up period (R2 = 26%; P<0.001). Eyes with more severe disease at baseline were also more likely to have a decrease in NEI VFQ-25 scores during follow-up (P<0.001). For subjects with the same amount of change in SAP sensitivity, those with shorter follow-up times had larger changes in NEI VFQ-25 scores (P = 0.005). A multivariable model containing baseline and rate of change in binocular MS had an adjusted R2 of 50% in predicting change in NEI VFQ-25 scores. Baseline severity, magnitude, and rates of change in BVF sensitivity were associated with longitudinal changes in QoL of glaucoma patients. Assessment of longitudinal visual field changes may help to identify patients at greater risk for developing disability from the disease.